Formation and interaction patterns in social crowdsourcing environments. (1st January 2013) - Schall, Daniel
Over the past years, the web has transformed from a pool of statically linked information to a people-centric web. Various web-based tools and social services have become available enabling people to communicate, coordinate, and collaborate in a distributed manner. In this work, we consider social crowdsourcing environments that are based on the capabilities of human-provided services (HPS) and software-based services (SBS). Unlike traditional crowdsourcing platforms, we consider collaborative environments where people and software services jointly perform tasks. We propose formation and interaction patterns that are based on social principles. The idea of our social crowdsourcing approach is that interactions emerge dynamically at runtime based on social preferences among actors. The evolution of interactions is guided by a monitoring and control feedback cycle to recommend competitive compositions and to adjust interaction behaviour. Here we present fundamental formation patterns including link mesh and broker-based formations. We discuss the prototype implementation of our service-oriented crowdsourcing framework.